Ethno-religious rivalry in Nigeria: causes and effects (1993-2015) - Mohammed, Isah Shehu (2020)
Ethno-religious rivalry has crept into the heterogeneous, major and minority groups and every part of Nigerian system, but overshadowed by related conflicts among others. Despite the Constitution and other policy checks being enforced, rivalry has been escalating among the groups. Therefore, Nigeria with a population of over 193 million people is embroiled in the rivalry which often leads to many negative trends. This study explored the ethno-religious rivalry in Nigeria from 1993-2015 with objectives of exploring the causes; the effects on Nigeria; and the ways to lessen it. A qualitative study method was used with in-depth and open ended interviews using nonprobability sampling. The study used the system and pluralism theories. In-depth interviews were conducted with experts and stakeholders on the central phenomenon in all the 6 geo-political zones of Nigeria. The findings revealed that colonialism, poverty, imbalanced socio-economic development, resource competition and conflict, historical heterogeneities, manipulation of religion and ethnicity by the elites, the role of military, non-adherence with the rule of law have been responsible for the ethnoreligious rivalry in Nigeria; ethno-religious rivalry has impacted in both positive and negative ways, and become entrenched among the majority groups of Nigeria; that it cannot be completely stopped, but lessened. In order to lessen it, the study recommended that the traditional, political religious and social institutions would have to rise up and enlighten the people, uphold values of justice, good brother and neighbourhood, tolerance, dialogue and accommodation of one another; while the Nigerian state authorities must ensure adherence with the rule of law, controlled preaching, balanced distribution of socio-economic resources and functional education to citizens, good governance, and strict implementation of the federal character principles and provisions. The study contributed in expanding the methodologies of studying the central phenomenon, analysis and the reported findings; and in addition, explored other latent issues in ethno-religious set up in Nigerian. The Nigerian populace and authorities would benefit from the findings of this study in further strengthening the forces of unity among Nigerian, especially at this critical moment of multi-dimensioned threats to the corporate existence and sustenance of the united Nigeria.